Accurate positioning for automatic car parking system - Wong, Natalie Zi Wei (Nanyang Technological University, 2022)
There has been an increase in the importance of Global Positioning System (GPS) coordinates partly due to the development of autonomous vehicles, thus there is a need to ensure that the GPS coordinates are accurate. However, in cities like Singapore, there are many high-rise buildings which can affect the accuracy of the GPS coordinates such as multipathing. This project aims to identify the type of data that could be used in order for the vehicle to accurately park in a parking lot. And through several testing, it was found that the most suitable type of data for the accurate positioning would be data points where the vehicle is moving slowly. It was also found that a slow-moving vehicle would give a average inaccuracy of half a lot while a fast moving would give an average inaccuracy of an entire parking lot.